2014
DOI: 10.1104/pp.114.240648
|View full text |Cite
|
Sign up to set email alerts
|

Proton Gradient Regulation5-Like1-Mediated Cyclic Electron Flow Is Crucial for Acclimation to Anoxia and Complementary to Nonphotochemical Quenching in Stress Adaptation  

Abstract: To investigate the functional importance of Proton Gradient Regulation5-Like1 (PGRL1) for photosynthetic performances in the moss Physcomitrella patens, we generated a pgrl1 knockout mutant. Functional analysis revealed diminished nonphotochemical quenching (NPQ) as well as decreased capacity for cyclic electron flow (CEF) in pgrl1. Under anoxia, where CEF is induced, quantitative proteomics evidenced severe down-regulation of photosystems but up-regulation of the chloroplast NADH dehydrogenase complex, plasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 72 publications
(116 reference statements)
6
64
2
Order By: Relevance
“…7B). PGRL1-dependent PSI-CEF has been proposed to be crucial for acclimation and survival in anoxic conditions under a constant light regime, both in Physcomitrella patens and C. reinhardtii (Kukuczka et al, 2014). In our experimental conditions, growth of pgrl1 mutant was not impaired (Fig.…”
Section: Concomitant Absence Of Hydrogenase Activity and Pgrl1-dependmentioning
confidence: 48%
“…7B). PGRL1-dependent PSI-CEF has been proposed to be crucial for acclimation and survival in anoxic conditions under a constant light regime, both in Physcomitrella patens and C. reinhardtii (Kukuczka et al, 2014). In our experimental conditions, growth of pgrl1 mutant was not impaired (Fig.…”
Section: Concomitant Absence Of Hydrogenase Activity and Pgrl1-dependmentioning
confidence: 48%
“…It has been demonstrated that efficient CEF is crucial for successful acclimation to excess light (Munekage et al, 2004;Dang et al, 2014;Johnson et al, 2014;Kukuczka et al, 2014). The most rapid response to excess light, however, relies on a mechanism called nonphotochemical quenching (NPQ).…”
mentioning
confidence: 99%
“…In P. patens, PGR5/PGRL1-dependent cyclic electron flow appears to operate, based on analyses using the pgrl1 knockout mutant [39 ]. Interestingly, it is also suggested that PGRL1 is required for survival under high light and anoxic conditions in C. reinhardtii and P. patens and thus might have been essential for plant terrestrialization [39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it is also suggested that PGRL1 is required for survival under high light and anoxic conditions in C. reinhardtii and P. patens and thus might have been essential for plant terrestrialization [39 ]. The NDH complex is absent in green algae and some gymnosperms but present in P. patens.…”
Section: Introductionmentioning
confidence: 99%